It is a small world : Crac Alsace catalogue 2002-2003. - Cattini, Sandra; Dazord, Cécile; Nefkens, Han; Teerlinck, Hilde; Varadinis, Mirjam (Altkirch : CRAC (Centre Rhenan d'Art Contemporain) Alsace Altkirch, 2004)
Capllonch, Biel ; Murphy, Karen ; Komen, A.P. ; Nollen, Arno ; Cantor, Ellen ; N.I.C.J.O.B. ; Rondinone, Ugo ; Haines, David ; Chatelain, Philippe ; Lislegaard, Ann ; Ström, Annika ; Cuenca Rasmussen, Lilibeth ; Asaoka, Akané ; Planas, Esther ; Banz, Stefan ; Bartoloméo, Joël ; Boon, Elke ; Molacek, Rudi ; Weiss, Erich ; Hilden, Thyra ; Strömbeck, Lisa ; Kaap, Gerald Van Der ; Copers, Leo ; Martin, Josep Maria ; Friedl, Peter ; François, Michel ; Lericolais, Rainier ; Nova, Nils ; Müller, Josh ; Duyvendak, Yan ; Galler, Thomas ; Roos, Maya ; Grommek, Joachim ; Mistiaen, Carlo ; Markowitsch, Rémy ; Broodthaers, Marcel ; de Cordier, Thierry ; Strba, Annelies ; Kawara, On ; Grigely, Joseph ; Meister, Ulrich ; Huet, Elodie ; Sommerlatt, Sophie ; Immelé, Anne ; Chartrier, Sylvain ; Pfeiffer, Vincent ; Pagic, Slobodan ; Martinez Oliva, Jesus ; Belouin, Pierre ; Nydegger, Anita ; Kemp, Kristine ; Blanca, Paul ; Abad, Francesc ; Badiola, Txomin ; Busto, Anna ; Dean, Tacita ; Fischer, Roland ; Pey, Marcel ; Malagrida, Anna ; Hirakawa, Noritoshi ; Moffatt, Tracey ; Peral, Alberto ; Olivares, Sergio ; Serrano, Andres ; Sherman, Cindy ; Torres, Francesc ; Smith, Terry ; Gartentor, Heinrich ; Garcia-Alix, Alberto ; Wall, Jeff ; Graham, Dan
Duits
Engels
Frans
boek